Pseudoartrosi settiche e asettiche dell’arto inferiore - Salomone, C.; Burastero, G.; Antonini, A.; Carrega, G.; Biasibetti, A.; Riccio, G. (Lo Scalpello - Journal, 2019)
ASEPTIC AND SEPTIC NONUNIONS IN LOWER LIMBNonunion is a dangerous orthopaedic complication. The purpose of this work was to provide an indication for thediagnosis, classification and treatment of nonunions. The technique for treating aseptic nonunions depends onviability of the site. Therapeutic intervention create a mechanical and biological situation positive to achieve thetreatment. In septic cases, the method consists in oncological debridement of bone and soft tissue and reconstructivesurgery. Circular fixation plays an active role.